Growth of the american kitchen - Cottrell, Martha Amelia (My University, 1894)
Introduction: As the heart by its ceaseless throbbing sends the stream of life through every part of the human system carrying disease or health, so the influence from the kitchen brings to the entire household weal or woe. No matter how the heart is affected, the whole system is similarly affected; and according to the working of the kitchen, the entire household is ruled. This has been true in past years, it is true of the present, and can we expect it to be less true in the future? As the power of the kitchen is more and more realized, changes for the better are made, not only in the utensils, but in the foods. The kitchen, therefore keeps pace with the general advancement of the country, in influencing and in turn being influenced by it. The first woman had one advantage over the rest of womankind, her husband could not compare her food with his mothers, yet she was justly blamed where sorrow followed after he partook of the food she offered him. From that day to this moreover woman has been censured for offering all too frequently injurious rather than good food. To realize the great progress in household economy, let us compare the past with the present and take a glance into the future. To appreciate the kitchen of today let us go back to our grandmothers.
Citation: Cottrell, Martha Amelia. Growth of the american kitchen. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Kitchen; Appliances; Home economics; Interior design; Architecture; Theses; Manuscripts (documents)